Factors that Influenced The Decision Making of Public High School Students in Bangkok to Study in Bachelor’s Degree, International Program - สัมฤทธิ์, วัลลภา (Journal of Humanities and Social Sciences, Rajapruk University, 2017)
The objectives of this study were to study factors that influenced the decision making of public high school students in Bangkok to study in Bachelor’s Degree, international program, and to compare the marketing factors that influenced the decision to study in Bachelor’s Degree, international programs clarified by demographic with in a different characteristics such as gender, average grade point, family income types, and need to pursue higher education. Research Methodology: The samples consisted of high school students who study in public high schools in Bangkok by using of 400 Multi-stage Random Samplings which were utilized as the main data collection and using further analysis into statistical information by t-test and Anova. Research findings were as follows: 1) Factors that influenced the decision making of public high school students in Bangkok to study in Bachelor’s Degree, International Program, considering that all aspects are important at high level. The elements of the institute is as important as the number one, followed by the Process and People involved with students respectively. 2) Public High School Students with different average grade point emphasize vary in Promotion and Productivity Factors 3) Public High School Students with different program interest emphasize vary in Promotion and People involved with students Factors. 4) Public High School Students with different family income emphasize vary in Price Factor.